2015
DOI: 10.3324/haematol.2014.118497
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD9 participates in dysmegakaryopoiesis and stromal interactions in primary myelofibrosis

Abstract: ABSTRACTof CD9 expression which precedes the appearance of GPIIb/IIIa. 16 We have previously demonstrated that CD9 participates in normal megakaryopoiesis and platelet formation through its action on megakaryocyte demarcation membrane separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…[12][13][14] Once localized in the proximity of marrow sinusoids, MKs are surrounded by a different environment and can either migrate or extend proplatelets through the endothelial barrier. Previous studies have reported that MKs migrate toward an SDF-1a gradient; however, the intracellular processes that regulate MK migration are not well known 9,11,[15][16][17] and constitute a gap in our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Once localized in the proximity of marrow sinusoids, MKs are surrounded by a different environment and can either migrate or extend proplatelets through the endothelial barrier. Previous studies have reported that MKs migrate toward an SDF-1a gradient; however, the intracellular processes that regulate MK migration are not well known 9,11,[15][16][17] and constitute a gap in our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CD9 and CD151 are engaged in thrombopoiesis, CD9 also affects myelopoiesis and CD151 erythropoiesis. These activities essentially depend on the association with integrins and include the crosstalk with the ECM and mesenchymal stem cells [107111]. We noted reduced CD62P, TER119 and GR1 expression in Tspan8ko and CD151ko BMC.…”
Section: Discussionmentioning
confidence: 77%
“…Wt-TEX can support this process by CD184 induction, possibly in concert with additional chemokine receptors [115, 116]. A direct contribution to CD184 expression was described for CD9, CD184 upregulation modulating megakaryocyte motility and leukemia dissemination [107, 117]. Furthermore, a CD63 mutant inhibits HIV1 entry by disrupting the trafficking of CD184 to the plasma membrane [118].…”
Section: Discussionmentioning
confidence: 99%
“…The signal intensities from single experiment raw data lists are normalized by dividing the intensities values by their median. Normalized data were accessible on public database: (GEO submission number GSE44426 , http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE44426 ), online on Jan. 10, 2015) [1] , [2] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%